Novel functions of integrated stress response proteins on collided ribosomes - Chan, Tristan Yew Kit (Nanyang Technological University, 2024)
Ribosome stalling during translation can lead to ribosome collisions, providing a platform for the ribosome-associated quality control (RQC) and the integrated stress response (ISR) pathways. RQC dissociates stalled ribosomes through Hel2-mediated ubiquitylation of the small ribosome subunit protein uS10, while ISR represses translation initiation by eIF2α phosphorylation. Gcn2 is the sole eIF2α kinase in Saccharomyces cerevisiae, whose activity requires two additional proteins, Gcn1 and Gcn20, which together form the GCN complex. Both the GCN complex and Hel2 bind collided ribosomes, raising the question of whether the GCN complex could influence Hel2-mediated RQC. This study reveals that Gcn1 and Gcn20 inhibit Hel2-mediated uS10 ubiquitylation, thereby repressing RQC. While a previous report suggested that Gcn2-mediated eIF2α phosphorylation may indirectly counteract RQC, this study demonstrates a direct interference by Gcn1 and Gcn20 with the Hel2-mediated RQC initiation. Notably, this novel function is independent of the Gcn2 kinase. ISR is robustly triggered in response to amino acid depletion. However, the GCN complex consistently inhibits Hel2, irrespective of amino acid availability. The GCN complex may protect transiently colliding ribosomes from RQC, allowing them to successfully complete ongoing translation.